Inclusivity of Thematic Park as a Public Space in Bandung City - Sugiana, Ervan; Kustiwan, Iwan (European Publisher, 2019)
Inclusive public space is a place that easily accessible by all people, and no one feels excluded there. In 2014, Bandung City developed a thematic park concept in several park locations. City parks as public open spaces should be able to use by all groups, especially women, children, the elderly, and people with disabilities. The development of thematic parks changes facilities in the park and changes the characteristics of park users. Therefore, it is necessary to know the level of thematic park inclusiveness as an evaluation of the development of public spaces in the city of Bandung. This research identifies indicators and the level of inclusiveness of public open space in the city of Bandung. We conducted observational surveys and questionnaires at the thematic and public parks/squares and to determine the level of inclusiveness and public perception of the inclusiveness of the space. We measure various types of access and visitor characteristics. Based on the analysis of the inclusiveness level of public open spaces in Bandung, non-thematic parks are considered slightly more inclusive than thematic parks, but thematic parks have higher visit frequency. The slight difference in the level of inclusivity indicates that there is potential for the development of thematic parks to be more inclusive by improving physical access and activities.